Lowering Mutant Huntingtin Levels and Toxicity: Autophagy-Endolysosome Pathways in Huntington's Disease - Valionyte, Evelina; Yang, Yi; Roberts, Sheridan L.; Kelly, Jack; Lu, Boxun; Luo, Shouqing (Journal of molecular biology, 2020)
Huntington's disease (HD) is a monogenetic neurodegenerative disease, which serves as a model of neurodegeneration with protein aggregation. Autophagy has been suggested to possess a great value to tackle protein aggregation toxicity and neurodegenerative diseases. Current studies suggest that autophagy-endolysosomal pathways are critical for HD pathology. Here we review recent advancement in the studies of autophagy and selective autophagy relating HD. Restoration of autophagy flux and enhancement of selective removal of mutant huntingtin/disease-causing protein would be effective approaches towards tackling HD as well as other similar neurodegenerative disorders. [Display omitted] •Huntington's disease (HD) is a monogenetic neurodegenerative disease, a model of neurodegeneration with protein aggregation.•Lowering mHTT levels alleviates mHTT toxicity and HD pathology.•Autophagic clearance reduces mHTT levels and toxicity.•Enhancing autophagic flux is an effective approach to tackle HD pathology.